2020
DOI: 10.1038/s41598-020-57973-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term metabolic consequences of acute dioxin exposure differ between male and female mice

Abstract: epidemiological studies have consistently shown an association between exposure to environmental pollutants and diabetes risk in humans. We have previously shown that direct exposure of mouse and human islets (endocrine pancreas) to the highly persistent pollutant TCDD (2,3,7,8-tetrachlorodibenzop-dioxin) causes reduced insulin secretion ex vivo. Furthermore, a single high-dose of TCDD (200 µg/kg) suppressed both fasting and glucose-induced plasma insulin levels and promoted beta-cell apoptosis after 7 days in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 48 publications
7
47
1
Order By: Relevance
“…We previously showed that CYP1A1 is induced and functional in human and mouse pancreatic islets following exposure to the highly persistent dioxin 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD, also referred to as dioxin) in vitro [ 8 ]. Cyp1a1 was also upregulated in mouse islets after systemic TCDD administration in vivo [ 8 , 9 ], indicating that dioxins reach the endocrine pancreas, which may impact beta cell function and survival. Indeed, TCDD-exposed mouse and human islets had significantly reduced glucose-induced insulin secretion in vitro [ 8 ], and a single high-dose injection of TCDD (20 μg/kg) reduced plasma insulin levels for up to 6 weeks in male and female mice in vivo [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that CYP1A1 is induced and functional in human and mouse pancreatic islets following exposure to the highly persistent dioxin 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD, also referred to as dioxin) in vitro [ 8 ]. Cyp1a1 was also upregulated in mouse islets after systemic TCDD administration in vivo [ 8 , 9 ], indicating that dioxins reach the endocrine pancreas, which may impact beta cell function and survival. Indeed, TCDD-exposed mouse and human islets had significantly reduced glucose-induced insulin secretion in vitro [ 8 ], and a single high-dose injection of TCDD (20 μg/kg) reduced plasma insulin levels for up to 6 weeks in male and female mice in vivo [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we and others have shown that dioxin suppresses insulin secretion in rodent islets ( 73 , 79 , 80 ) and human islets ( 73 ). Interestingly, acute high-dose dioxin exposure caused β-cell apoptosis in male mice but not female mice ( 81 ), whereas prolonged low-dose dioxin exposure led to impaired β-cell adaptation to high fat diet feeding in female but not male mice ( 74 , 82 ).…”
Section: Toxicity Testing In Pancreatic β-Cellsmentioning
confidence: 99%
“…Acute dioxin exposure led to long-term metabolic consequences in mice [59]. Organochlorine pesticides may potentially mediate insulin resistance [60].…”
Section: Effect Of Environmental Pollutants On Lipid Levels and Cardimentioning
confidence: 99%